KAJIAN HISTOLOGI OVARIUM IKAN SIDAT, Anguilla bicolor McClelland, YANG TERTANGKAP DI SEGARA ANAKAN CILACAP - Farida Nur Rachmawati; Untung Susilo (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2012)
The aim of this research was to know the histology of eel ovary, Anguilla bicolor McClelland, at various gonad developmental stage, which caught at Segara Anakan Cilacap. This research was conducted with survey method, there are 69 samples, about 47.1–76.5 cm in length and 143.6–982.5 g in weight. The parameters are gonad weight, histological structure and gonad maturation level. The result show that all of eels is female, which in yellow eel, and presilver stage. As the result, it can be concluded that Anguilla bicolor McClelland which caught at Segara Anakan Cilacap is immature, whereas mature stage of eel is not found.